For 5x+y=1, you would subtract 5x from each side, so you would get y=1-5x For 3x+2y=2, you would subtract 3x from each side, and then divide by 2. 2y=2-3x y=1-(3/2)x
2x +1 = 5x-2 2x +3= 5x 3 = 3x x=1
(4x - 1) (3x + 2)
3x+1+2x-2 = 64 3x+2x = 64-1+2 5x = 65 x = 13
-5x^2 - 55x - 120
3x2 + 5x + 2 is a quadratic expression that can be factored as follows: 3x2 + 5x + 2 = 3x2 + 3x + 2x + 2 = 3x(x + 1) + 2(x + 1) = (3x + 2)(x + 1)
3x+2 = 5x so 2x = 2 and hence x = 2/2 = 1
6x^2 + 5x + 1 = (3x +1) (2x + 1)
3x + 5x = 2x + 28x = 2x + 26x = 2x = (2/6) = 1/3
For 5x+y=1, you would subtract 5x from each side, so you would get y=1-5x For 3x+2y=2, you would subtract 3x from each side, and then divide by 2. 2y=2-3x y=1-(3/2)x
2x +1 = 5x-2 2x +3= 5x 3 = 3x x=1
3x + 2 + 2x = 7; 3x + 2x = 5x, so 5x + 2 = 7; 7-2=5, so 5x=5. 5x divided by 5 and 5 divided by 5 equals 1, so x equals 1.
(4x - 1) (3x + 2)
3x+1+2x-2 = 64 3x+2x = 64-1+2 5x = 65 x = 13
2(3x + 4) + 5x - 2
(5x 2 - 8x + 1) + (2x 2 - 4x - 11)
-5x^2 - 55x - 120